DAMPAK PENYULUHAN PROGRAM KRPL TERHADAP PERUBAHAN PERILAKU ANGGOTA KWT DWI SRI DALAM BUDIDAYA SAYURAN ORGANIK - Geba, Fernando Seda; Suwasono, Son; Asnawi, Dwi (Fakultas Pertanian, 2019)
Member of Dwi Sri KWT who cultivates organic vegetables in Dadaprejo Village with the aim of increasing income, agricultural productivity, and improving their welfare. This study aims to determine the level of change in behavior before and after counseling the KRPL program in cultivating organic vegetables. The population in this study were all members of Dwi Sri KWT who cultivated organic vegetables in Dadaprejo Village, which numbered 30 people. The sample is 28 members of Dewi Sri KWT using the Slovin formula. Data were analyzed descriptively quantitatively. The results showed that the level of behavior change of KWT Dewi Sri members before and after counseling from the attitude aspect before counseling (10.7%) amounted to 3 people with agreed categories and after counseling (57.1%) totaling 16 people with the agreed category. Knowledge aspects before counseling (28.6%) amounted to 8 people with the know category and after counseling (50.0%) totaling 14 people with the tofu category. Skill aspects before counseling (17.9%) amounted to 5 people in the skilled category and after counseling (71.4%) there were 20 people with the skilled category. The factors that significantly influence changes in behavior of KWT Dewi Sri members are age with a range of 41-50 years (46.4%) totaling 13 people. Anggota KWT Dwi Sri membudidayakan sayuran organik di Kelurahan Dadaprejo dengan tujuan untuk meningkatkan pendapatan, produktifitas, dan kesejahteraan hidupnya. Penelitian ini bertujuan untuk mengetahua tingkat perubahahan perilaku sebelum dan sesudah penyuluhan program KRPL dalam budidaya sayuran organik. Populasi dalam penelitian ini adalah seluruh anggota KWT Dwi Sri yang membudidayakan sayuran organik berjumlah 30 orang menggunakan rumus slovin. Data dianalisis dengan cara deskriptif kuantitatif. Hasil penelitian menunjukkan bahwa tingkat perubahan perilaku anggota KWT Dwi Sri sebelum dan sesudah penyuluhan dari aspek sikap sebelum penyuluhan (10,7%) berjumlah 3 orang dengan kategori setuju dan sesudah penyuluhan (57,1%) berjumlah 16 orang dengan kategori setuju. Aspek pengetahuan sebelum penyuluhan (28,6%) berjumlah 8 orang dengan kategori tahu dan sesudah penyuluhan (50,0%) berjumlah 14 orang dengan kategori tahu. Aspek keterampilan sebelum penyuluhan (17,9%) berjumlah 5 orang dengan kategori terampil dan sesudah penyuluhan (71,4%) berjumlah 20 orang dengan kategori terampil. Faktor yang berpengaruh nyata terhadap perubahan perilaku anggota KWT Dwi Sri adalah umur dengan kisaran 41-50 tahun (46,4%) berjumlah 13 orang.